Hubungan Tingkat Kepatuhan Dokter Dan Perawat Terhadap Standar Pelayanan Ispa Balita Dengan Kepuasan Keluarga Pasien Pada Bp Puskesmas Di Kabupaten Magelang - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
ABSTRACT Health services in community health centers should be managed professionally, of high quality. To fulfil the need and demand of quality health service, the health care unit community health center held therapy services according to the procedure and health service standard which had to be obeyed by doctors and nurses as a professional resources to get patients families satisfaction. This study was aimed to know the health service quality of doctor and nurse at the health care unit community health center toward ISPA Balita patients according to health service standard This study was held at six community health centers in Magelang regency. The subject of the study were doctors, nurses, and ISPA balita patient's families who accompanied to the healthcare unit at the community health centers. Type of this study was non-experimental using cross sectional approach. To analyze difference test using chi square and t-test, to test relation association using product moment correlation. The results showed that generally there was no difference between the obedience of doctor and nurse in giving service to ISPA Balita patients, but especially there were significant difference in therapy, physic examination, anamnesis done by doctor and nurse at the healthcare unit the community health center of Muntilan I, Kaliangkrik and Mertoyudan I. There was no difference families' satistaction of doctor or nurse in giving service to ISPA Balita patients. There was positive relationship between the obedience of doctor or nurse and the families' satisfaction of ISPA Balita patients with correlation coefficient doctor (r=0.847), nurse (r=0,929). The increasement of the obedience of doctor and nurse toward health service standard ISPA Balita at the health care unit community health center increased the patients families satisfaction.